Digital transformation know how : connecting digital transformation, agility and leadership - Viaene, Stijn, ....- (Leuven : Acco, 2020)
"In recent years, digital development has accelerated and digital turbulence is the new normal. So, it's time for a synthesis, time to bring stability to that turbulence: What have we learned? What do we know? What should we no longer have doubts about? Whether you're a CEO or a dedicated worker, you have an important role to play in your organisation's digital transformation. But it's hard when you don't have a common frame of reference or common language. What's the big picture? How do things align? How can you contribute? This book offers you a practical perspective on six critical elements of successful digital transformation design"
Keywords: Ondernemingen ; toekomst